THE EFFECTIVENESS OF TALKING CHIPS TECHNIQUE TO IMPROVE SPEAKING SKILL - Sulaiman, Masagus; Hartati, Sri; Anggraini, Anggi (English Community Journal, 2024)
This research aimed at figuring out whether or not it is effective to use talking chips technique in speaking English in descriptive text. This research applied a quantitative research design in line with true experimental research approach and 180 students of 6 classes to be the population and 64 of them were selected as the samples using purposive sampling technique. To collect the data, the researchers used test in the form of oral test. To analyze the data, the researchers used paired sample t-test and independent sample t-test. The results showed that The scores of posttest in experimental class was higher than control class with sig 0.00 < 0.05, which means that alternative hypothesis (Ha) was accepted and null hyphothesis (Ho) was rejected. In other words, talking chips technique was effective in teaching speaking English in descriptive text to the eighth grade students of SMP Negeri 9 Prabumulih.